Kitosan Sebagai Bahan Edible Coating Buah Stroberi (Fragaria x ananassa) Terhadap Jamur Rhizopus Stolonifer Penyebab Penyakit Busuk Lunak - Anita Dewi; Satriyo Restu Adhi; Fauzia Mustikasari (Universitas Respati Indonesia, 2025)
The soft rot disease caused by the pathogen Rhizopus stolonifer is one of diseases that causes significant losses during the storage and distribution of post-harvest fruit. The purpose of this study is to determine the effectiveness of using chitosan and its various concentrations in reducing soft rot disease in strawberries. The study was conducted in vitro at the Biotechnology Laboratory, Faculty of Agriculture, Universitas Singaperbangsa Karawang, from February to March 2025. The experiment use randomized complete block design with five treatments: control (K0), chitosan 0.5% (K1), chitosan 1% (K2), chitosan 1.5% (K3), fungicide (F) as the positive control, and each treatment was repeated five times with four samples each. The results showed that the 1.5% chitosan treatment (K3) had a significant impact on the disease severity treatments, and significantly affected the weight loss parameter, with the lowest weight loss value compared to other treatments. These findings suggest that chitosan, particularly at the consentration of 1.5%, is effective in controlling soft rot disease in strawberries during storage.